2012
DOI: 10.1093/europace/eus204
|View full text |Cite
|
Sign up to set email alerts
|

Metoprolol succinate vs. ivabradine in the treatment of inappropriate sinus tachycardia in patients unresponsive to previous pharmacological therapy

Abstract: Metoprolol and ivabradine exert a similar effect on resting HR in patients with IST. Ivabradine seems to be more effective to relieve symptoms during exercise or daily activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
13

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 28 publications
3
70
0
13
Order By: Relevance
“…The drug has no other hemodynamic effects aside from lowering the heart rate. As such, it has been investigated for use to reduce the sinus rate and improve symptoms related to IST (85)(86)(87)(88)(89)(90)(91)(92)(93).…”
Section: Ongoing Management: Recommendationsmentioning
confidence: 99%
“…The drug has no other hemodynamic effects aside from lowering the heart rate. As such, it has been investigated for use to reduce the sinus rate and improve symptoms related to IST (85)(86)(87)(88)(89)(90)(91)(92)(93).…”
Section: Ongoing Management: Recommendationsmentioning
confidence: 99%
“…There are controversy and a lack of consensus regarding the diagnostic criteria of this entity. It has been recently published in a case series comparing the effect of metoprolol and ivabradine [24] on resting HR and during exercise in IST patients. Ivabradine was more effective to relieve symptoms during exercise or daily activity and was better tolerated.…”
Section: Resultsmentioning
confidence: 99%
“…Cal o et al [22] in a case series that included 18 IST patients demonstrated the effects of ivabradine in reducing HR at the Holter recordings and to increasing the exercise tolerance in stress tests. Still, in another case series comparing the effect of metoprolol and ivabradine on resting HR and during exercise in IST patients, ivabradine was more effective in relieving symptoms during exercise or daily activity and was better tolerated [23].…”
Section: Inappropriate Sinus Tachycardiamentioning
confidence: 90%